ECONOMIC EVALUATION OF UNDERGROUND GOLD MINING CUT AND FILL METHOD AT PT XYZ USING REAL OPTION METHOD: COMPARISON OF DISCOUNTED CASH FLOW, MONTE CARLO, BINOMIAL LATTICE AND FUZZY BINOMIAL LATTICE APPROACHES - Nuraini, Zafira
Discounted Cash Flow (DCF) is a very common method used to analyze the feasibility of a project, including in the mining industry which has capital-intensive and risk-intensive characteristics. However, the uncertainty factor and management flexibility in decision making are not considered by the DCF method. So that an analysis is carried out using a Monte Carlo simulation and the Real Option Valuation (ROV) method to accommodate these two factors to produce the right investment decisions. The decision-making process for the DCF method considers the Net Present Value (NPV) and Internal Rate of return (IRR). Then a deterministic sensitivity analysis will be carried out to determine the most influential parameter in a project on the NPV value and a Monte Carlo simulation will be carried out to obtain the probability of the NPV value of the project. After that, it will be analyzed using the ROV method with two approaches, namely the binomial lattice and fuzzy binomial lattice to see the options that can be formed from the project to assist in the decision-making process. From the results of the feasibility analysis carried out, it shows that with the DCF method, the NPV value is $11,167,803.86 and the IRR is 21.08%, so it can be said that this mining project is economically feasible. From the results of the deterministic sensitivity analysis, it is known that the selling price parameter has the most significant influence on the project's NPV value. Meanwhile, from the Monte Carlo simulation, the average NPV value for the three periods is -$4,257,659.76 with a positive NPV probability of 32.43%. Based on the ROV binomial lattice method, this project will have an option value only for the inflation parameter, while with the fuzzy binomial lattice option value is obtained for the three parameters in each period.